STRATEGY FOR CULTIVATION OF DISCIPLINE CHARACTER THROUGH PRIVATE DHUHA PRAYER IN JAMA'AH - Faina, F; Mujiburrohman, M (Institut Islam Mamba'ul 'Ulum Surakarta, 2023)
This study aims to determine the strategy of cultivating students' disciplinary character through the habit of praying dhuha in congregation. This research is a qualitative research. The subject of this study was at MI Islamiyah Senting, Sambi sub-district, Boyolali Regency. Collecting data in this study using observation, interviews and documentation. While the steps for data analysis are three stages that must be done in analyzing qualitative research data, namely data reduction, data presentation and verification. The results of the study show that the disciplined character of students can be formed with the role of education, including through habituation, understanding, and exemplary